The Implementation of K13 Curriculum in Madrasah Aliyah in The South West Region of Aceh (English Teachers’ Perspectives) - Erizar; Tuti Hidayati; Sari Diana (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2021)
Teacher's perception of the K-13 is believed to be one of the factors that lead to the success or failure of the curriculum implementation. This is because the K-13 makes teachers have to adjust and change the learning style in the classroom. Considering the various phenomena about the K-13, the researcher was interested in conducting research the Implementation of the K-13 in the South West Region of Aceh (English Teachers’ Perspectives). In this research, the researchers also analyzed some obstacles faced by the English Teachers in implementing the K-13 and what solutions offered by STAIN Teungku Dirundeng Meulaboh as one of the universities which produce the teachers in the South West Region of Aceh. The research applied quantitative and qualitative approach that involved 21 English teachers who teach English at Madrasah across South West of Aceh. The result of the study indicated that the implementation of K-13 has not been effective due to several reasons such as the allocation time is insufficient and too many forms of assessment. Moreover, the English teachers issued that the biggest obstacle in implementing the K-13 was the excessive administrative demands. Therefore, the government of Indonesia, in this matter, the Deparment of Education has to ascertain that the majority of English teachers receive training related to K-13 and review the time allocation provided to the English teachers. For the English teachers, they should be creative and innovative in improving their understanding on K-13 using printed and online resources.